2016
DOI: 10.1371/journal.pone.0157602
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetyl Cysteine May Support Dopamine Neurons in Parkinson's Disease: Preliminary Clinical and Cell Line Data

Abstract: BackgoundThe purpose of this study was to assess the biological and clinical effects of n-acetyl-cysteine (NAC) in Parkinson’s disease (PD).MethodsThe overarching goal of this pilot study was to generate additional data about potentially protective properties of NAC in PD, using an in vitro and in vivo approach. In preparation for the clinical study we performed a cell tissue culture study with human embryonic stem cell (hESC)-derived midbrain dopamine (mDA) neurons that were treated with rotenone as a model f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
84
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 56 publications
1
84
1
Order By: Relevance
“…These side effects were mild to moderate and reversible, resolving within a few days or weeks of stopping NAC. It is possible that the adverse events are dose dependent, as investigators using a lower dose (1200 mg NAC/day) did not observe worsening of parkinsonian symptoms, but instead patients who took 1200 mg/day in combination with weekly intravenous dosing reported symptomatic improvement . A major difference between our study and that conducted by Monti et al was that the latter study used weekly intravenous doses in combination with relatively low oral daily doses.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…These side effects were mild to moderate and reversible, resolving within a few days or weeks of stopping NAC. It is possible that the adverse events are dose dependent, as investigators using a lower dose (1200 mg NAC/day) did not observe worsening of parkinsonian symptoms, but instead patients who took 1200 mg/day in combination with weekly intravenous dosing reported symptomatic improvement . A major difference between our study and that conducted by Monti et al was that the latter study used weekly intravenous doses in combination with relatively low oral daily doses.…”
Section: Discussioncontrasting
confidence: 53%
“…Long‐term oral administration of NAC in a PD mouse model substantially reduced neuronal loss, oxidative stress, and motor abnormalities . Recently, a combination intravenous/oral NAC therapy was reported to decrease symptoms in individuals with PD …”
mentioning
confidence: 99%
“…A recent publication has demonstrated that the glutathione precursor, NAC, produced a mean 13% improvement in UPDRS scores, and significantly increased DAT density in the caudate and putamen in PD, suggesting that NAC and/or GSH can affect dopaminergic neurotransmission [28]. In addition to having potential as a disease-modifying agent, these data support the idea that (in)GSH may also have symptomatic efficacy.…”
Section: Discussionsupporting
confidence: 53%
“…We previously reported findings from cell line data and preliminary clinical effects of N‐acetyl‐cysteine (NAC), which suggested possible improvements in dopamine transporter (DAT) binding in a small number of patients with PD who received NAC, using ioflupane DaTscan single photon emission computed tomography (SPECT) imaging . Three months of NAC treatment resulted in increased DAT binding in the basal ganglia; hence, the present study extends those results with a more robust study number and comprehensive analyses.…”
mentioning
confidence: 99%
“…In the pilot study mentioned above, we used ioflupane DaTscan SPECT imaging and the Unified Parkinson's Disease Rating Scale (UPDRS) scores to assess whether there was any positive signal from the NAC treatment. The primary goals of the present study were to provide expanded data regarding the effect of NAC administration on DAT binding and symptoms in patients with PD.…”
mentioning
confidence: 99%